Protótipo de uma plataforma web para reserva de horários na quadra da Escola Municipal de Ensino Fundamental Pe. Lourenço Scotti - ASSUNÇÃO, Luan de Araújo (2024)
The software sector in Brazil is constantly growing, driven by the demand for technological solutions in various areas, reaching a revenue of over R$ 238.2 billion in 2021, according to ABES. With this growth, reservation software has become a necessity for institutions that wish to offer online booking services. In this sense, this article describes the development of a prototype web system to computerize the reservation process for the court at the Municipal Elementary School Pe Lourenço Scotti, which is currently managed manually, without a formal procedure or proof of reservation for customers. The goal is to offer a more efficient and convenient experience for customers and facilitate reservation management for the institution.